1989
DOI: 10.1177/019262338901700106
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Vasculitis

Abstract: There are .several naturally occurring and iatrogenic models of vasculitis available in animals, although few have primary coronary vessel lesions. Aleutian disease of mink and equine viral arteritis are 2 well studiednaturaldiseases whichmaybe produced experimentally and, thus, makegoodanimalmodels. Several drugs have beenidentified which produce myocardial lesions, including vasculitis, in susceptible individuals o~whe? given in highenough doses. Immune mediatedmechanisms are probably amongthe most important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…In rats, the lesions involved small mesenteric arteries (Joseph et al, 1996b;Zhang et al, 2002), while in dogs, the site of arteriopathy was exclusively the coronary arteries and/or the heart muscle (Isaacs et al, 1989;Dogterom and Zbinden, 1992). Both rats and dogs are thought to have increased susceptibility to drug-induced vascular lesions due to the common occurrence of spontaneous arteriopathies in these species (Bishop, 1989, Ruben et al, 1989Mitsumori, 1990). Literature on vascular disease in monkeys is sparse.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, the lesions involved small mesenteric arteries (Joseph et al, 1996b;Zhang et al, 2002), while in dogs, the site of arteriopathy was exclusively the coronary arteries and/or the heart muscle (Isaacs et al, 1989;Dogterom and Zbinden, 1992). Both rats and dogs are thought to have increased susceptibility to drug-induced vascular lesions due to the common occurrence of spontaneous arteriopathies in these species (Bishop, 1989, Ruben et al, 1989Mitsumori, 1990). Literature on vascular disease in monkeys is sparse.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been no reports of mesenteric vasculitis in patients treated with roflumilast N-oxide or another orally active PDE4 inhibitor cilomilast, widely used in patients with asthma and COPD in phase 3 clinical trials (FDA website). It is therefore plausible that rats and dogs have an increased susceptibility to drug-induced vascular lesions because such arteriopathies commonly occur in these species (used regularly in preclinical toxicology studies [117,118]), with differences across species in terms of both PDE4 expression and the functional effects of PDE4 inhibitors. For example, a recent study demonstrated that levels of PDE4 activity in many tissues are much higher in rats than in humans, which would explain why rats are more susceptible to PDE4 inhibitor-induced toxicities [119].…”
Section: Clinical Datamentioning
confidence: 99%
“…Spontaneous arterial diseases of the dog have been described by Kelly (26) who pointed out that degenerative and proliferative arterial diseases are either age-related or have well-recognized associations with other diseases. In dogs, inflammatory vascular changes have been caused by a variety of infectious agents (bacteria, fungi, and parasites) or immunemediated processes (3,38,39), but these spontaneous lesions are rarely encountered in nonclinical safety assessment studies, given the pathogen-free status of the dogs. One type of spontaneous arterial change that can pose problems in evaluating potential drug-induced vascular changes is idiopathic polyarteritis of Beagle dogs.…”
Section: Spontaneous Vascular Injury In Dogmentioning
confidence: 99%